Basic properties evaluation of alkyl palmitate to be used as oil insulation. Issue 1 (July 2020) - Rajab, A; Ramadhani, J S; Kurniawan, R; Qibran, K; Melda, L; Hamid, M I
Abstract: This paper discusses the evaluation of alkyl palmitate to be used as the oil insulation in an oil-filled transformer. Three kinds of alkyl palmitates, namely, Methyl-, Ethyl-, and Isopropyl-palmitates, were prepared through the esterification of methyl-, ethyl-, and iso-propyl-alcohols, respectively, and palmitate acid. The resulted alkyl palmitates were then evaluated for their basic properties such as breakdown voltage, viscosity, density, acidity, and water content based on the ASTM D 6871 standard specification. The peroxide value of the alkyl palmitates was also examined to indicate their oxidation stability and compared the result with that of mineral oil. The results show that viscosity, water content, and density of all alkyl palmitates fulfill the values specified by the standard, whereas, the breakdown voltage and acidity do not. The peroxide value of all alkyl palmitates is still much higher than that of mineral oil.